A novel function of junctional adhesion molecule-C in mediating melanoma cell metastasis - Langer, Harald; Orlova, Valeria V.; Xie, Changping; Kaul, Sunil; Schneider, Darius A.; Lonsdorf, Anke Susanne; Fahrleitner, Manuela; Choi, Eun Young; Dutoit, Vanessa; Pellegrini, Manuela; Grossklaus, Sylvia; Nawroth, Peter Paul; et al. (Cancer research, 2011)
Hematogenous dissemination of melanoma is a life-threatening complication of this malignant tumor. Here, we identified junctional adhesion molecule-C (JAM-C) as a novel player in melanoma metastasis to the lung. JAM-C expression was identified in human and murine melanoma cell lines, in human malignant melanoma, as well as in metastatic melanoma including melanoma lung metastasis. JAM-C expressed on both murine B16 melanoma cells as well as on endothelial cells promoted the transendothelial migration of the melanoma cells. We generated mice with inactivation of JAM-C. JAM-C−/− mice as well as endothelial-specific JAM-C-deficient mice displayed significantly decreased B16 melanoma cell metastasis to the lung, whereas treatment of mice with soluble JAM-C prevented melanoma lung metastasis. Together, JAM-C represents a novel therapeutic target for melanoma metastasis.